Substantial increase in mutations in the genes pfdhfr and pfdhps puts sulphadoxine–pyrimethamine‐based intermittent preventive treatment for malaria at risk in Burkina Faso. Issue 6 (27th March 2014) - Geiger, Carolin; Compaore, Guillaume; Coulibaly, Boubacar; Sie, Ali; Dittmer, Martin; Sanchez, Cecilia; Lanzer, Michael; Jänisch, Thomas
Abstract Objective Sulphadoxine–pyrimethamine (SP) is widely used as intermittent preventive treatment (IPT) for malaria in pregnant women in Sub‐Saharan Africa. There are reports of wide‐spread SP resistance in countries where SP had once been used as a first‐line treatment. It is unclear whether the development of SP resistance also affects countries where SP is mainly used in the context of IPT, as is the case in Burkina Faso. To assess the efficacy of SP‐based IPT, we monitored the prevalence of SP conferring genetic mutations in the genes dhfr and dhps in Plasmodium falciparum populations in a rural area of Burkina Faso over a period of 13 years. Methods Molecular epidemiological study consisted of six consecutive cross‐sectional surveys of rainy and dry seasons (2009–2012). Data from the rainy season in 2000 served as a baseline. Mutations in dhfr and dhps associated with SP resistance were analysed by pyrosequencing in 861 parasite‐positive samples. Results The prevalence of the SP resistance conferring triple dhfr mutation 51I, 59R, 108N increased from 1.3% in the rainy season of 2000 to 35.3% in 2009, and 54.3% in 2011 (P ≤ 0.001). Comparing rainy and dry seasons, we observed an increasing step‐like pattern with higher prevalence of the dhfr triple mutant in the respective dry season compared with the preceding rainy season. The proportion of the dhps 437Gly mutation in the rainy season of 2000 was 53.2% and subsequently increased to 77.6% in 2009 (P ≤ 0.001). Conclusion The increase in molecular markers linked with SP resistance jeopardises the efficacy of IPTp and the planned IPTi interventions in Burkina Faso, calling for careful monitoring of genotypic resistance markers and in vivo validation of IPT efficacy.